2015
DOI: 10.1007/s11104-015-2610-6
|View full text |Cite
|
Sign up to set email alerts
|

The fate of fertiliser P in soil under pasture and uptake by subterraneum clover – a field study using 33P-labelled single superphosphate

Abstract: Background and aims Single superphosphate (SSP) is a major source of phosphorus (P) used in grazing systems to improve pasture production. The aim of this experiment was to determine the fate of fertiliser P in clover pastures under field conditions. Methods A procedure was developed to radiolabel SSP granules with a 33 P radiotracer, which was then applied to the soil surface (equivalent to ~ 12 kg P ha -1 ) of a clover pasture. Recovery of fertiliser P was determined in clover shoots, fertiliser granules and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 78 publications
(114 reference statements)
0
6
0
Order By: Relevance
“…This benefit is observed in the longer term (Oliveira et al., 2019), in a manner similar to its use as a P correction source. In these situations, crop nutrition depends little on recently applied P fertilizer, where soil is the main provider of P to the plants (Mclaren et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This benefit is observed in the longer term (Oliveira et al., 2019), in a manner similar to its use as a P correction source. In these situations, crop nutrition depends little on recently applied P fertilizer, where soil is the main provider of P to the plants (Mclaren et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…During a growing season, only a small fraction of the P added to a soil is removed at harvest time, leaving a fraction of it available for subsequent crops (McLaren et al, 2016). That fraction is called the residual value of the P applied (Syers et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Gains are being made through better management practices, such as improved matching of plant need and supply of fertilizer applications. However, McLaren et al ( 2015 ) demonstrated that the majority of the fertilizer P applied to two Australian pasture soils became sorbed to the soil in inorganic and organic P pools, with only 35% being taken up by clover plants in the year of application. Therefore, there is interest in ways to make the soil P more bioavailable using plant traits (Faucon et al 2017 ; Kidd et al 2016 ; Wendling et al 2016 ), microbial cycling (Richardson and Simpson 20211 ), and, more recently, intercropping (Xue et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%